2012
DOI: 10.1002/nur.21489
|View full text |Cite
|
Sign up to set email alerts
|

The Chicago Parent Program: Comparing 1‐year outcomes for African American and Latino parents of young children

Abstract: Data were merged from two prevention randomized trials testing 1-year outcomes of a parenting skills program, the Chicago Parent Program (CPP), and comparing its effects for African-American (n=291) versus Latino (n=213) parents and their preschool children. Compared to controls, intervention parents had improved self-efficacy, used less corporal punishment and more consistent discipline, and demonstrated more positive parenting. Intervention children had greater reductions in behavior problems based on parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 48 publications
5
97
0
13
Order By: Relevance
“…In the initial RCT evaluation with low-income African-American and Latino parents, those who participated in the Chicago Parent Program reported less frequent use of physical punishment and more frequent expressions of warmth toward their children compared to the control group (Gross et al, 2009). A second RCT evaluation, which combined the findings from the initial evaluation with a separate, larger sample, the program was again found to be effective at reducing physical punishment, as well as reducing teacher-rated externalizing and internalizing behavior problems over the subsequent year (Breitenstein et al, 2012). …”
Section: Programs Targeting Parentsmentioning
confidence: 99%
“…In the initial RCT evaluation with low-income African-American and Latino parents, those who participated in the Chicago Parent Program reported less frequent use of physical punishment and more frequent expressions of warmth toward their children compared to the control group (Gross et al, 2009). A second RCT evaluation, which combined the findings from the initial evaluation with a separate, larger sample, the program was again found to be effective at reducing physical punishment, as well as reducing teacher-rated externalizing and internalizing behavior problems over the subsequent year (Breitenstein et al, 2012). …”
Section: Programs Targeting Parentsmentioning
confidence: 99%
“…The program has been widely disseminated and implemented in day care centers, Head Start and other early childhood intervention programs. Financial support to develop, test and disseminate the intervention was supported by the Robert Wood Johnson Foundation and the National Institutes of Health (Breitenstein et al, 2012;Gross et al, 2009Gross et al, , 2014.…”
Section: Nurse Exemplars Of Evidence-based Practice That Address Dispmentioning
confidence: 99%
“…There is a long and fruitful history of nurse investigators developing interventions that have demonstrated efficacy in improving health, reducing healthcare costs, and generating other desirable outcomes across a wide array of populations. Some examples include interventions to reduce HIV risk behaviors among racial and ethnic minority adolescents 64 ; and to improve parenting skills across culturally and ethnically diverse populations, 65,66 disease self-management skills among adolescents and teens with Type I diabetes mellitus, 67 and coping and psychosocial health responses of parents of hospitalized/critically ill children or premature infants. 68 Each of these exemplar EBI’s have demonstrated outcomes using rigorous study designs; hence, they represent EBIs with high evidence ratings for implementation in practice settings and could greatly improve healthcare and population health if implemented on a large scale nationwide.…”
Section: Advancing Dandi Research Through and For The Nursing Disciplinementioning
confidence: 99%